Anthelmintic and Cytotoxic Activities of Two Medicinal Plants: Polygonum viscosum and Aphanamixis polystachya Growing in Bangladesh - Amin, M. N.; Majumder, M. S.; Moghal, M. M. R.; Banik, S.; Kar, A.; Hossain, M. M. (Journal of Scientific Research, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> The present study was designed to investigate in vitro anthelmintic and cytotoxic activities of crude methanolic extract of two plants(Polygonum viscosum and Aphanamixis polystachya) grown in Bangladesh. Evaluation of cytotoxic activity was done using the brine shrimp lethality bioassay. The crude methanolic extract of Polygonum viscosum showed significant cytotoxic potential (LC50 value of 6.34 ?g/ml) among all the fractions comparing with that of standard vincristine sulphate (0.825 ?g/ml). Besides, the LC50 values of crude methanolic extract, pet ether and chloroform extracts of Aphanamixis polystachya showed good cytotoxic activities 11, 10.36, and 16.45 µg/ml, respectively. The other study was undertaken to evaluate anthelmintic activity (using Pheretima posthuma model) where piperazine was used as reference standard. The crude methanolic extract of Polygonum viscosum leaves produced a significant anthelmintic activity in dose dependent manner and the activity of crude extract was comparable with that of standard drugs. Besides, the Aphanamixis polystachya extract revealed moderate anthelmintic activity. Here, the anova testing was done with the P < 0.05. Further studies are suggested to determine the active compounds responsible for the anthelmintic and cytotoxic activities of these two plant extracts. Keywords: Anthelmintic; Cytotoxic; Medicinal plant; Aphanamixis polystachya; Polygonum viscosu. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i2.17299 J. Sci. Res. 6 (2), 339-345 (2014)